Anatomy education environment among pre-clinical medical students in Universiti Putra Malaysia using anatomy education environment measurement inventory - Gunn, Shyeanne Shian Yen; Mohd Jalani, Siti Aisyah; Rushlan, Muhammad Aliff Aiman; Hadie, Siti Nurma Hanim; Minhat, Halimatus Sakdiah; Abas, Razif (Penerbit Universiti Sains Malaysia, 2021)
Anatomy is the foundation of medicine. Having adequate anatomy knowledge would improve medical students’ comprehension of pathology and patient management. The evolving scenario in anatomy education has created a changing educational environment in medical schools. Since educational environment influence the students’ motivation and ability to learn, it is pertinent to measure anatomy education environment as a feedback mechanism tool for further improvement in the curriculum. This study was performed to measure pre-clinical medical students’ perception of the anatomy education environment in Universiti Putra Malaysia (UPM) by using a validated 25-item inventory, known as the Anatomy Education Environment Measurement Inventory (AEEMI). The inventory was distributed online to 171 first- and second-year medical students to measure their perception of anatomy teachers and instructors, anatomy knowledge, their intrinsic interest and efforts in learning anatomy, anatomy learning resources and histology practical facilities. The analysis revealed that most of the items show “positive area” indicated by score of more than four. The first-year medical students showed a significantly higher perception of the anatomy education environment compared to the second-year medical students (p ≤ 0.05). However, both cohorts perceived an “area of improvement” for histology practical facilities (score of 3 to 3.99). In conclusion, the students were pleased with the anatomy education experience in UPM except for histology practical facilities that may require further improvement. The use of virtual microscopy in histology teaching would be a good alternative to overcome the problem in histology teaching in UPM, especially during the COVID-19 pandemic.